Changes in haematological and biochemical blood parameters of C57Bl/6 mice in acute paracetamol poisoning - A. I. Zudova; E. A. Mukhlynina; I. F. Gette; L. V. Solomatina (Сибирский научный медицинский журнал)
Paracetamol is one of the five most common drugs causing fatal hepatotoxicity. The mouse model of paracetamol hepatotoxicity adequately reflects the mechanism of drug poisoning in humans. However, there are many controversies associated with understanding the pathogenetic mechanisms of process.   Aim of the study was to reveal the signs of systemic damage of various organs on the basis of estimation of haematological and biochemical indices of peripheral blood of experimental animals after administration of a half-year dose of paracetamol.   Material and methods. Male C57Bl/6 mice aged 10 weeks were given a single intraperitoneal injection of a paracetamol solution at a concentration of 14 mg/ml at a dose of 600 mg/kg body weight or saline in an equivalent volume, after 6, 12, 24 and 48 hours, blood was collected and haematological and biochemical analysis were performed.   Results and discussion. Paracetamol administration causes in mice an increase in alanine and aspartate aminotransferase activity, decrease in total protein, albumin, globulin content. There is an increase in the urea and creatinine level. Transient monocytopenia, lympho- and thrombocytopenia, granulocytosis are observed in peripheral blood.   Conclusions. After administration of paracetamol at a dose of 600 mg/kg body weight, signs of liver (change of alanine and aspartate aminotransferase activity, total protein and urea content) and kidney (creatinine level) dysfunction were detected in mice. In peripheral blood, the classic picture of inflammatory response is determined (lymphopenia and granulocytosis) with signs of impaired haemostasis in the form of thrombocytopenia. No generalized changes affecting all organs were detected, which determines the need to use more sensitive and specific methods to detect signs of systemic inflammation.